Stress undermines reward-guided cognitive performance through synaptic depression in the lateral habenula - Nuno Perez, Alvaro (2021)
Weighing alternatives during reward pursuit is a vital cognitive computation that, when disrupted by stress, yields aspects of neuropsychiatric disorders. To examine the neural mechanisms underlying these phenomena, we employed a behavioral task in which mice were confronted by a reward and its omission (i.e., error). The experience of error outcomes engaged neuronal dynamics within the lateral habenula (LHb), a subcortical structure that supports appetitive behaviors and is susceptible to stress. A high incidence of errors predicted low strength of habenular excitatory synapses. Accordingly, stressful experiences increased error choices while decreasing glutamatergic neurotransmission onto LHb neurons. This synaptic adaptation required a reduction in postsynaptic AMPA receptors (AMPARs), irrespective of the anatomical source of glutamate. Bidirectional control of habenular AMPAR transmission recapitulated and averted stress-driven cognitive deficits. Thus, a subcortical synaptic mechanism vulnerable to stress underlies behavioral efficiency during cognitive performance.